The Implementation of the Singaporean Model in Kazakhstan: Applying or Appealing? - Amanbekov, Timur (Nazarbayev University School of Sciences and Humanities, 2020)
The use of the Singaporean model was adopted by the government of Kazakhstan in 1995 with the approval of the Second Constitution, partially due to the ideas of Nursultan Nazarbayev, who considered this model to be beneficial to the post-independence state development. The Singaporean model is based on the Japanese model of “Iron Triangle”, i.e. the mixture of formal and informal networks fusing bureaucracy, politics and private sector. This implies heavy government intervention in the market, authoritarian regulations of the legal and private sectors, as well as central planning. The economy itself relies on three major aspects, such as geostrategic locations, manufactured export, and foreign direct investments. The state is run by a neo-patrimonial government, formed around Lee Kuan Yew, and, after his death, around his son and current prime minister Lee Hsien Loong. On the other hand, the social welfare is operated by the means of co-optation, as the Lee Kuan Yew administration introduced semi-socialist measures, such as public housing and healthcare, which is believed to balance the authoritarianism and silence opposition. The success of the model can be observed in the economic indexes, like Singapore, while being a city-state and 176th biggest country in the world, in 2019, had the 8th largest GDP per capita of $64 thousand, 0.935 Human Development Index, and the 11th largest foreign exchange reserve.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects